2013
DOI: 10.1111/1365-2435.12191
|View full text |Cite
|
Sign up to set email alerts
|

Grazing alters insect visitation networks and plant mating systems

Abstract: Summary1. Many flowering plant species have a facultative or obligate dependence on insect pollination for reproductive success. Anthropogenic disturbance may alter these species interactions, but the extent to which structural changes to plant-pollinator networks affect plant species mating systems is not well understood. 2. We used long-term livestock grazing of a birch wood ecosystem to test whether disturbance of this semi-natural habitat altered floral resources, the structure of plant-insect visitation n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 51 publications
6
110
1
7
Order By: Relevance
“…Previous works showed that the disturbances generated by human activity caused pollinator and plant diversity declines worldwide [5][6][7][8][9][10][11]. One of the main human-disturbance that may affect plant-pollinator interactions is the introduction of livestock for grazing in natural areas [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works showed that the disturbances generated by human activity caused pollinator and plant diversity declines worldwide [5][6][7][8][9][10][11]. One of the main human-disturbance that may affect plant-pollinator interactions is the introduction of livestock for grazing in natural areas [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Sociality is another trait affecting vulnerability to landscape alteration. Social bees are central location foragers tied to the colony location, consequently they are more sensitive to the distance to forage resource patches in the surrounding landscape [20 ,38] than nonsocial insects with free-living progeny, such as Diptera [38,39 ]. Even within social bee taxa, species-specific differences in mobility and dispersal range will govern responses to habitat loss and/or fragmentation.…”
mentioning
confidence: 99%
“…With many tree species being animal pollinated (at least in tropical systems), the genetic diversity and fitness of progeny of woody plants sired in fragmented landscapes are expected to decline due to shifts in plant-mating patterns (for example, reduced outcrossing rate and/or pollen diversity due to habitat fragmentation and/or changes in pollinator community composition and behavior, Vanbergen et al, 2013). This hypothesis is tested by Breed et al (2015a) in a case study of three ecologically divergent Eucalyptus tree species, and from a meta-analysis of the literature.…”
Section: Overview Of the Focal Issue Studiesmentioning
confidence: 99%
“…A continued focus on these three areas is likely to be scientifically fruitful and deliver real progress on management strategies for trees in impacted landscapes. In particular, a more quantitative approach to linking changes in pollination to mating systems to fitness is likely to yield important insights on the mechanisms driving the changes we observe (for example, Vanbergen et al, 2013). We look forward to reviewing new hypotheses, developments and latest research in this area in 10 years time!…”
mentioning
confidence: 98%